Extended Theoretical Framework of Parental Internet Mediation: Use of Multiple Theoretical Stances for Understanding Socio-Ecological Predictors - Iqbal, Sarosh; Zakar, Rubeena; Fischer, Florian (Frontiers in Psychology, 2021)
The phenomenon of digital media is common in contemporary societies. Recognizing the popularity of digital online devices amongst the younger generation, the subject of parental internet mediation is of utmost significance for avoiding adverse effects of digital media on youngsters’ physical, cognitive and social well-being. Taking insights from an informed review of multi-grounded theories, we propose an extended framework of socio-ecological predictors related to parental internet mediation. This contribution offers an innovative methodological and analytical perspective to consider both psychological and behavioral predictors for promoting resilience. This paper acknowledged resilience as a strength-based measure to ensure online safety amongst young individuals. This paper suggests that an integrated socio-ecological approach is critical to formulate the basis for a theoretical framework to fully comprehend socio-ecological predictors of parental internet mediation.